2017
DOI: 10.1515/cclm-2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, calibration and evaluation of the First International Standard for human C-peptide

Abstract: Background: Measurement of C-peptide by immunoassay contributes to the diagnosis of a number of disorders related to β cell function. Stocks of the current international reference reagent (IRR) for C-peptide, used to calibrate these immunoassays, are exhausted, and this report summarises the international study to establish a replacement World Health Organization (WHO) international standard (IS) to maintain the availability of a globally available reference material and support efforts to standardise C-peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The candidate standard was also shown to have appropriate immunological activity in the immunoassay systems included in the study. C-peptide is measured clinically in serum/plasma and urine, and so, using a difference in bias approach (27)in ten of these immunoassay systems to assess the commutability of the candidate standard with serum and urine samples, it was additionally shown that with the exception of two of these assays the candidate standard demonstrated commutability with respect to the serum and urine samples included in the study (30). The First International Standard for C-peptide is now available from NIBSC.…”
Section: Efforts To Harmonize C-peptide Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The candidate standard was also shown to have appropriate immunological activity in the immunoassay systems included in the study. C-peptide is measured clinically in serum/plasma and urine, and so, using a difference in bias approach (27)in ten of these immunoassay systems to assess the commutability of the candidate standard with serum and urine samples, it was additionally shown that with the exception of two of these assays the candidate standard demonstrated commutability with respect to the serum and urine samples included in the study (30). The First International Standard for C-peptide is now available from NIBSC.…”
Section: Efforts To Harmonize C-peptide Resultsmentioning
confidence: 99%
“…Each ampoule of the material contains 8.64 μg of C-peptide with an expanded uncertainty of 0.43 μg. Since the material is solely intended to be used as a reference material for immunoassays, it was sent to manufacturers of C-peptide immunoassay methods and shown to be commutable with serum samples for 8 of 10 commercially available immunoassays (30). …”
Section: Efforts To Harmonize C-peptide Resultsmentioning
confidence: 99%
“…A likely explanation is that, as polypeptides, C-peptide and insulin may behave differently in pure solution than in a sample-matrix solution. The first international standard for human C-peptide (WHO ISR 13/146) and its international reference reagent (WHO IRR84/510) were reported to be incommutable for some measurement systems [ 12 , 16 ]. Comparability of C-peptide and insulin measurements between laboratories and measurement systems was effectively improved using one low-level and one high-level pooled sample to recalibrate clinical measurement systems, as reported previously [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…C-peptide and insulin are the important products in proinsulin enzymatic cleavage that secreted into the circulation in equimolar concentrations [51]. C-peptide and insulin levels were decreased significantly in diabetes rats.…”
Section: Discussionmentioning
confidence: 99%